Discovery of Pyrrolidine-2,3-diones as Novel Inhibitors of P. aeruginosa PBP3 - Arancha López-Pérez; Stefan Freischem; Immanuel Grimm; Oliver Weiergräber; Andrew J. Dingley; María Pascual López-Alberca; Herbert Waldmann; Waldemar Vollmer; Kamal Kumar; Cuong Vuong (MDPI AG, 2021)
The alarming threat of the spread of multidrug resistant bacteria currently leaves clinicians with very limited options to combat infections, especially those from Gram-negative bacteria. Hence, innovative strategies to deliver the next generation of antibacterials are urgently needed. Penicillin binding proteins (PBPs) are proven targets inhibited by β-lactam antibiotics. To discover novel, non-β-lactam inhibitors against PBP3 of Pseudomonas aeruginosa, we optimised a fluorescence assay based on a well-known thioester artificial substrate and performed a target screening using a focused protease-targeted library of 2455 compounds, which led to the identification of pyrrolidine-2,3-dione as a potential scaffold to inhibit the PBP3 target. Further chemical optimisation using a one-pot three-component reaction protocol delivered compounds with excellent target inhibition, initial antibacterial activities against P. aeruginosa and no apparent cytotoxicity. Our investigation revealed the key structural features; for instance, 3-hydroxyl group (R2) and a heteroaryl group (R1) appended to the N-pyrroldine-2,3-dione via methylene linker required for target inhibition. Overall, the discovery of the pyrrolidine-2,3-dione class of inhibitors of PBP3 brings opportunities to target multidrug-resistant bacterial strains and calls for further optimisation to improve antibacterial activity against P. aeruginosa.